Brand image and consumer satisfaction towards Islamic travel packages: A study on tourism entrepreneurship in Malaysia. Issue 2 (30th September 2019) - Nawi, Noorshella Binti Che; Al Mamun, Abdullah; Nasir, Noorul Azwin Md; Abdullah, Azwan; Mustapha, Wan Nurulasiah Wan
Abstract : Purpose: This study aims to examine the factors affecting brand image and consumer satisfaction towards Islamic travel package in Malaysia. Design/methodology/approach: This study used a cross-sectional design and quantitative method in examining the factors affecting the brand image and consumer satisfaction on Islamic travel package. This study has chosen Google form as a platform to collect the data. Findings: The findings revealed that product quality, Islamic physical attribute and Islamic belief have a significant positive effect on brand image and consumer satisfaction. The findings confirmed that product quality, Islamic physical attribute and Islamic beliefs are the crucial tools for brand image that leads to the satisfaction of Muslim consumers on the Islamic travel package. Originality/value: This paper addresses understudied aspects of brand image and consumer satisfaction towards Islamic travel package in Malaysia. It provided useful insights into the product quality, Islamic physical attribute and Islamic belief on brand image and consumer satisfaction towards Islamic travel packages. Tourism companies should improve and update their package based on the religious perspective to attract Muslim consumers.